Influence of Fiber Volume and Fiber Length on Thermal and Flexural Properties of a Hybrid Natural Polymer Composite Prepared with Banana Stem, Pineapple Leaf, and S-Glass - K. B. Prakash; Yahya Ali Fageehi; Rajasekaran Saminathan; P. Manoj Kumar; S. Saravanakumar; Ram Subbiah; B. Arulmurugan; S Rajkumar (Advances in Materials Science and Engineering)
There is more demand for natural fiber-reinforced composites in the energy sector, and their impact on the environment is almost zero. Natural fiber has plenty of advantages, such as easy recycling and degrading property, low density, and low price. Natural fiber’s thermal properties and flexural properties are less than conventional fiber. This work deals with the changes in the thermal properties and mechanical properties of S-glass reinforced with a sodium hydroxide-treated pineapple leaf (PALF) and banana stem fibers. Banana stem and pineapple leaf fibers (PALF) were used at various volume fractions, i.e., 30%, 40%, and 50%, and various fiber lengths of 20 cm, 30 cm, and 40 cm with S-glass, and their effects on the thermal and mechanical properties were studied, and their optimum values were found. It was evidenced that increasing the fiber volume and fiber length enhanced the flexural and thermal properties up to 40% of the fiber volume, and started to decrease at 50% of the fiber volume. The fiber length provides an affirmative effect on the flexural properties and a pessimistic effect on the thermal properties. The PALF S-glass combination of 40% fiber load and 40 cm fiber length provides maximum flexural strength, flexural modulus, storage modulus, and lowest loss modulus based on hybrid Taguchi grey relational optimization techniques. PALF S-glass hybrid composite has been found to have 7.80%, 3.44%, 1.17% higher flexural strength, flexural modulus, and loss modulus, respectively, and 15.74% lower storage modulus compared to banana S-glass hybrid composite.